Searching for Dubh: Experiments in Black Dyes Pre 15th Century in Ireland and Scotland - Ashley Stillwell-Hasan (EXARC Journal)
This paper explores sources of black dyes in Ireland and Scotland prior to 1500, in order to better understand the extent to which they were used and the hues that can be produced. I propose that it is possible to obtain true blacks using only natural dyeing techniques. To test this hypothesis, four variations of historically plausible dye methods, and a control, were tested based on the availability of the dyestuffs. Brown Shetland wool was dyed according to possible historical methods, and each variant was subjected to a series of tests to examine lightfastness and wash fastness. Initially, testing showed a low indigotin content, an organic compound which creates a blue pigment, in the sourced woad, resulting in a poor dye bath and skewed results. The woad-based samples were repeated using a modern method of extracting indigotin from woad due to limitations in sourcing and time. Each dye sample was subjected to a long-term light exposure test utilizing blue wool standard cards for comparison, in addition to two different wash and rub tests. The two samples that were created using woad as a base dye and produced the richest shades of black with the least amount of apparent damage to the fibers. Closer examination showed that the addition of alum resulted in substantial degradation of the fleece and made it difficult to spin. Additionally, all samples proved to be lightfast. Further testing is required of the other plausible recipes collected, in addition to repeat testing using the more historical methods in this experiment. However, this experiment did show that lightfast black colour was possible to produce prior to the import of logwood.